A novel control scheme to mitigate temperature profile variation in a SOFC System. (November 2022) - Chen, Jinwei; Hu, Zhenchao; Zhang, Huisheng
Abstract: Maintaining temperature profile in a solid oxide fuel cell (SOFC) is one of the essential issues that need to be addressed during the load tracking. In this paper, a novel control scheme with three-loop structure is developed to mitigate SOFC temperature profile variation. This scheme can simply implemented by three variable-speed blowers. The first blower is an anode recirculation blower used to maintain anode inlet temperature, the second one is a cathode recirculation blower used to maintain cathode inlet temperature, and the last one is an air blower used to maintain cathode outlet temperature. Compared with other simple schemes with only one-loop or two-loop structure, the scheme with three-loop structure achieves the best performance in mitigating SOFC internal temperature profile variation and guaranteeing a safe margin on operation limits. With a 10% system load step drop, the three-loop control scheme presents the best performance in rapidity and stability, with a much smaller overshoot, a much shorter settling time, and the smallest ITAE criterion. The SOFC temperature profile variation is also smallest (deviating within 4.7 K). Time-dependent temperature gradient is much less than 3.0 K/min. Temperature gradient is significant less than 10 K/cm. Steam to carbon ratio is also kept more than 2.0. Furthermore, the three-loop control scheme can perform high system efficiency, which reaches 53.9% at the 90% load. As a result, the three-loop SOFC temperature control scheme is robust in safe and efficient operation. Highlights: Mitigating SOFC temperature profile variation with three-loop control scheme. Three-loop scheme performing the best control performance. SOFC temperature profile varying within 4.7 K. SOFC temperature gradient much less than 10 K/cm. Three-loop scheme achieving highest system efficiency.